Analisis Dampak Peningkatan Air Larian (Run Off) Pada Tahap Konstruksi dan Operasi di Pabrik Sepatu PT.X Kabupaten Cirebon - Alif Illyasa Putra Yuswandi; Eka Wardhani (Jurnal Serambi Engineering, 2024)
Population development in Cirebon Regency has led to increased land use, resulting in a reduction in water catchment areas, which is one of the factors causing inundation. One of the factors that causes puddles is running water or runoff due to rainfall and rain intensity that exceeds the speed of the soil's absorption capacity. In this research, measurements were made of the increase in runoff water discharge during the construction and operation stages of PT. X. PT. X has a land area of 36.6 ha. The research locations are in the Priuk Block, Pabedilan Kulon Village, Pabedilan District, and the Plaza Block in Damarguna Village, Ciledug District, Cirebon Regency. So, it is necessary to carry out runoff water analysis, starting with hydrological analysis, to obtain rainfall intensity values. The I value was obtained at 152.30 mm/hour. The land used for construction and operations is rice fields and plantations, with a value of C = 0.5 for plantations and 0.8 for rice fields. The frequency used is 0.278. So, the result of increasing runoff water discharge for the construction and operation stages is 3,744 m3/sec.